Approaches to the thermal analysis of ship-based LNG tanks under harsh external environmental conditions - Vesalainen, Henry (2021)
This thesis investigates the usability of CFD modeling in LNG carrier hull thermal design. The study focuses on the membrane type of tank that is the most common tank-type in carrying LNG nowadays. Carrying LNG along the arctic sea roads exposes the hull structures to extreme cold temperatures because the heat flux through the tank structure is minor. The situation could be seen as an advantage from BOG's point of view but an increased challenge from the hull durability point of view. For fulfilling the requisites of hull steel parts, the thermal analysis must execute. In this way, the ship's safety operation is ensured, and the material cost in the construction phase is optimized. The main aim of this thesis is to execute thermal analysis for the carrier’s steel structure. IMO’s IGC code is a driving force in LNG carriers' design. It can be stated that the IMO’s regulations are not given practical help for designers. The more specific guidelines are established from classification societies, and these guidelines are helping the designer to achieve the requirements. The main part of the thesis states that executing manual 1-D calculations is a good way to achieve the calculation boundaries for the CFD model. The results from the CFD simulations are reasonable and coherent with manual calculations. The used mesh resolutions did not show a significant effect on temperature distributions of the inner hull. Based on the results, the steel grade design could be executed by using these modeling tools. CFD calculations were executed with ANSYS student license. Tässä diplomityössä kartoitetaan numeerisen virtausdynamiikan käytettävyyttä LNG tankkerin rungon rakenteen lämpötilajakauman määrittämiseksi. Tutkimuksessa keskitytään membraani tyypin tankkiin, joka on nykypäivänä käytetyin eristystapa LNG:n kuljetuksessa. LNG:n kuljetus läpi arktisten alueiden altistaa rungon rakenteita erittäin kylmille lämpötiloille, koska lämpövirta ympäristöstä rungon rakenteisiin on vähäistä. Tämä voidaan nähdä selkeänä etuna syntyvän ...